2008
DOI: 10.1529/biophysj.108.129155
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of Enzyme-Catalyzed Reactions with Disparate Timescales

Abstract: Many physiological characteristics of living cells are regulated by protein interaction networks. Because the total numbers of these protein species can be small, molecular noise can have significant effects on the dynamical properties of a regulatory network. Computing these stochastic effects is made difficult by the large timescale separations typical of protein interactions (e.g., complex formation may occur in fractions of a second, whereas catalytic conversions may take minutes). Exact stochastic simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 20 publications
3
64
0
Order By: Relevance
“…This method is termed stochastic QSSA. 20,43 Several studies in the deterministic setting have shown that the validity of the standard QSSA is limited to certain parameter conditions. Thus, the total quasi-steady state approximation (tQSSA) has been introduced as an alternate approximation with increased accuracy.…”
Section: Validity Of Lna Models Derived Using Stochastic Tqssamentioning
confidence: 99%
See 1 more Smart Citation
“…This method is termed stochastic QSSA. 20,43 Several studies in the deterministic setting have shown that the validity of the standard QSSA is limited to certain parameter conditions. Thus, the total quasi-steady state approximation (tQSSA) has been introduced as an alternate approximation with increased accuracy.…”
Section: Validity Of Lna Models Derived Using Stochastic Tqssamentioning
confidence: 99%
“…This has then been adapted in the stochastic setting where stochastic simulations of the CME are performed using the deterministic quasisteady state expressions of the fast variables obtained using the tQSSA. 20,43,46 There are several studies that investigate the validity of these stochastic quasi-steady state approximations. Particularly, the work by Kim et al demonstrates, via twodimensional systems modeled by the CME and LNA, that the tQSSA provides a better approximation to the original system in comparison to the standard QSSA.…”
Section: Validity Of Lna Models Derived Using Stochastic Tqssamentioning
confidence: 99%
“…8 Mastny et al 54 have carried out in-depth analysis of using QSSA under different conditions through the use of singular perturbation analysis. More recently, Barik et al 13 have extended the QSSA by analyzing the conditions under which the standard QSSA might fail. They have utilized the total QSSA ͑TQSSA͒ and have shown that under certain conditions the method of Rao and Arkin 8 fails.…”
Section: Reactions With Complex Rate Expressionsmentioning
confidence: 99%
“…Some of the more recent contributions in this area include ͑1͒ speed-up of computation through a binomial tauleaping approach 9 and k-skip method, 10 ͑2͒ time-scale/ reaction partitioning based on the propensity values, 11 a hybrid approach, 12 and quasi-steady-state approximation, 13 ͑3͒ partial-propensity-based approach, 14 and ͑4͒ alternative formulations of CLE. 15 Besides, Cai 16 has developed an approach to perform stochastic simulation of reaction systems with time-delays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation